The research on vocal technique, voice and singing in Interpretative Practices in Brazil: Analysis of the summaries of dissertations - Miguel, Fabio [UNESP]; Moutinho, Lucas Goncalves [UNESP]; Anselmi, Luis Guilherme [UNESP]; Janson, Silvio Fernando [UNESP]; Pedrozo, Willian Gomes [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2015)
This work discuss a partial of the study The Research in Vocal Technique, Voice and Singing: State-of-the-Art developed in 2012-2014 by GEPPEVOZIA (Research, study and practice on voice group from UNESP Institute of Art). It aims to investigate the state-of the art on the topics of vocal technique, voice and singing in different areas of knowledge. We presented the result of the analysis of the research in the fields of Music and Arts through the summaries of master's degree dissertations that deals with these topics. The search on CAPES' website was made by keywords. In this article we focused on the analysis of the resumes with which the studies were related to, direct or indirectly, on Performance Practice. Resumes showed some inconsistencies, although it is possible to understand the trends of voice related research.
Keywords: vocal technique; voice; singing; performance practice